If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7z + -3 = 1 + 9z Reorder the terms: -3 + 7z = 1 + 9z Solving -3 + 7z = 1 + 9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9z' to each side of the equation. -3 + 7z + -9z = 1 + 9z + -9z Combine like terms: 7z + -9z = -2z -3 + -2z = 1 + 9z + -9z Combine like terms: 9z + -9z = 0 -3 + -2z = 1 + 0 -3 + -2z = 1 Add '3' to each side of the equation. -3 + 3 + -2z = 1 + 3 Combine like terms: -3 + 3 = 0 0 + -2z = 1 + 3 -2z = 1 + 3 Combine like terms: 1 + 3 = 4 -2z = 4 Divide each side by '-2'. z = -2 Simplifying z = -2
| 28+24m=35+17m | | -3(7p+4)+-2(5+17p)+-3(4+4p)=0 | | 5y-6=6y-4 | | -7=q-7 | | 0=x^2+4x+9 | | 3m-24=45+6m | | 4(5x-3)+2(10-2x)=5(3x+2)-5 | | 1/5(x+9)=6 | | 11x+x= | | 3x+7x*7x-8x+6x*6x= | | 45(x+5)=0 | | 12a=b | | -3(7p+4)-2(5-17p)-3(4+4p)=0 | | 1=2x+0.5 | | 5(7c-1)-10=33c+5 | | 0=x^2-2x-7 | | -(9-6a)-(6+5a)-26=-(4-7a)+(-a)+3 | | a^2+4*a=45 | | 3(1-3b)=-6b+15 | | -3y-6y= | | 66-y=58 | | -5n+8=4m | | -8x-2x=12 | | 7+-2(-5x+-9)+2x=4(2x+-1)+3(x+12) | | -[6z-(9z+6)]=6+(2z+9) | | 7r=6r-84 | | (m-4)(3m+5)= | | (7c+9)(c+7)=47 | | 3(2x+2)+2(x-7)=x+13 | | 2r-4r+8+r= | | 2p^5-10p^3+14p^2=0 | | 5[z-(7z+66)+6]=2(z+10) |